BIOERODED AND OR ENCRUSTED AMMONITE MOULDS AND THEIR TAPHONOMIC IMPLICATIONS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2000)
Encrustation and/or bioerosion have been observed on both sides of several ammonites sampled from Lower-Middle Toarcian Rosso Ammonitico of the Umbria-Marche Apennines (Central Italy). The majority of these features are due to the activity of polychaete worms: the encrusting s.s. is due to serpulids, whilst bioerosion s. s. is similar to Maeandropolydora decipiens Voigt, and a third category of polychaetes has produced bioerosion-encrustation structures. The ornamentation features of the samples studied, allowed us to establish that the upper sides are preserved as composite moulds and the lower sides as internal moulds. The overprinting of the external shell structures on the internal infillings took place during burial diagenesis; the deformation style is plastic and only vertical, lateral deformation s being impeded. The presence of boring and/or encrustation on the lower side of internal moulds is classically interpreted as evidence of reelaboration. Regarding these Toarcian specimens, the nature of the composite moulds would seem to confirm that the phenomena of encrusting and/or boring by polichaete worms occurred before the dissolution of the shells. Except in the cases of pure bioerosion, it is impossible to ascertain whether the shell was already infilled or not. The encrustation by polichaete worms probably occurred during post-mortem drifting or when the shell was exposed on the sea floor. The similarity between the observed bioerosion phenomena and other hard and/or firm material borers gives us reason to think that the complete re-exhumation of the shell is not necessary to permit the boring action: however, a partial re-exhumation might have helped the borer to detect the presence of a shell test.